Inkjet‐printed multi‐color arrays based on eco‐friendly quantum dot light emitting diodes with tailored hole transport layer. Issue 10 (24th April 2022) - Zhan, Shijie; Suh, Yo‐Han; Fan, Xiang‐Bing; Yang, Jiajie; Ni, Limeng; Kim, Yoonwoo; Jo, Jeong‐Wan; Choi, Hyung Woo; Jung, Sung‐Min; Shin, Dong‐Wook; Lee, Sanghyo; Kim, Jong Min
Abstract: Cadmium‐free quantum dot light‐emitting diodes (QLEDs) have held the potential to revolutionize the next‐generation displays with their advantages in color gamut, luminance intensity, and solution processibility. As a promising way of realizing large‐area QLED display production, inkjet printing has been intensively studied on Cd‐based QLEDs but lacks exploration in fabricating Cd‐free devices. Here, we developed Cd‐free RGB inkjet‐printed QLEDs with tailored hole transport layers (t‐HTLs) using Cd‐free QDs including InP/ZnSeS red and green QDs and ZnTeSe/ZnSe/ZnS blue QDs. With the t‐HTLs, QD ink erosion on the bottom charge transport layer was remarkably suppressed, while the efficient hole transport was maintained, which kept high device performance, especially in the QLED lifetime. With bank structures, Cd‐free QLED pixels were well defined within the size of 60 μm × 160 μm. Based on the t‐HTL structure and the bank structures, inkjet‐printed Cd‐free RGB QLED pixel arrays were demonstrated. This study bridges the gap between existing Cd‐free QLED technologies and the future commercialization of Cd‐free self‐emissive QD displays. Abstract : A tailored hole transport layer is employed for QD‐LEDs through a comprehensive study on the jetting behaviour of QD inks and the interface between QDs and the transport layer. Inkjet‐printed RGB multi‐colour microscale arrays based on Cd‐free QD‐LEDs is realised.